O Brasil nos marcos do novo padrão exportador de especialização produtiva : uma verificação a partir dos dados de financiamento do BNDES e do orçamento de investimento da União no período de 2003 a 2014 - Magalhães, Sammer Dahir Siman (2016)
This work presents the financial support given by BNDES to Brazilian economy in the period of 2003-2014. It also, using data research, shows the Federal Government investments through the same years. These data and an evaluation that low-tech sectors prevails over Brazil and other Latin America Countries reinforce Jaime Osório s ‟ notion that these countries experience a new pattern of productive specialization of their exports. In this new model ” the exports axis constitutes, in general, sectors of global productive chain under the direction of transnational enterprises.” (Osório, 2009). This pattern of capital reproduction is the predominant in the region since the 70 s, an ‟ epoch of industrialization with a degree of autonomy. Osório s notion characterizes ‟ better Brazil s economic condition between 2003-2014 and advances in the comprehension ‟ of the country in terms of the preservation of its dependency condition. In this way, the New Export Pattern of productive specialization offers a more precise picture of this period, one that was called “post-neoliberal” or “neo-developmentist”. In the first chapter we debate Osórios theoretical propositions, that is, the New Export Pattern of productive specialization. Taking the notion of the pattern of capital s reproduction ‟ we locate Brazil in the terms of its dependency, highlighting the colonial past and the exogenous character of Brazilian economy that passes by five centuries of its revealed history. We also debate concepts like „super-exploition of workforce as an ‟ structuring element of the country, the oligarchyzation of Brazilian State, as well others aspects that help to locate the subordinated role of the country under the international labor s‟ division. In the second chapter we present aspects of Brazilian economy in the analized period (2003-2014). In the international arena, we identify China as a vector of global economy s growth that influences Latin America s growth. In relation to Brazilian ‟ ‟ economy, three distinct periods are identified: one (2003-2007), marked by an economic growth recovery; another (2008-2010), identified as a response to US 2008 economic crisis, and a third (2001-2014), marked by a period that Singer (2015) calls “development essay”. In the third chapter, we present the data of BNDES and the Invest Budget of Federal Government for these three periods (2003-2007; 2008-2010; 2011- 2014). In general terms, we identify that, analyzing BNDES data, infrastructure investments and basic basic material prevails over industrial inputs. In relation to the Federal Government s investments, 90% of it was put in the energy sector between ‟ 2003-2014. In the end, we conclude that Brail preserves its dependent character. To overcome this subordinated condition the country should reorient its development pattern, introducing an autochthonous model that derives from its people needs.